The influence of migration on dietary practices of Ghanaians living in the United Kingdom: a qualitative study - Hibbah Araba Osei-Kwasi; Katie Powell; Mary Nicolaou; Michelle Holdsworth (Taylor & Francis Group, 2017)
Background: Previous studies have identified a process of dietary acculturation when migrant groups adopt the food patterns of the host country. Aim: The aim of this study was to explore the influence of migration on dietary practices and the process of dietary acculturation amongst Ghanaians living in the UK. Subject and methods: A qualitative study of adults aged ≥25 years (n = 31) of Ghanaian ancestry living in Greater Manchester using face-to-face interviews. Participants varied in socioeconomic status, gender and migration status. Interviews were transcribed verbatim and analysed thematically. Results: Three distinct dietary practice typologies were discernible that differed in terms of typical meal formats, meal contexts, structure and patterning of meals, food preparation and purchasing behaviours: (i) continuity practices; (ii) flexible practices; and (iii) changed practices. The identified practices were shaped by interrelating factors that fell into four main clusters: social and cultural environment; accessibility of foods; migration context; and food beliefs/perceptions. Conclusion: Participants retained, to a varying degree, some aspects of Ghanaian dietary practices, whilst adopting key features of UK food culture. This study demonstrates the complexity of dietary change, indicating that it is not a linear process and it is dependent on several factors.